2017
DOI: 10.1007/s00404-017-4431-8
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone vs balloon catheter for labor induction in previous cesarean: a randomized controlled trial

Abstract: Clinical Trials Registry-India, www.ctri.nic.in , CTRI/2012/05/003634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 18 publications
2
20
0
9
Order By: Relevance
“…Previous CS done in our study for fetal distress in group A and B was 41.7% and 38.9% respectively comparable to Sharma et al 36%, Hemalatha et al 36.6%. 12,13 Previous CS done in our study for malpresentation was 30.6% and 33.3% in the two groups comparable to Sharma et al 30%, Hemalatha et al 13.3%. 12,13 In all these studies including the present study change in BS was found to be significant (Table 5).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Previous CS done in our study for fetal distress in group A and B was 41.7% and 38.9% respectively comparable to Sharma et al 36%, Hemalatha et al 36.6%. 12,13 Previous CS done in our study for malpresentation was 30.6% and 33.3% in the two groups comparable to Sharma et al 30%, Hemalatha et al 13.3%. 12,13 In all these studies including the present study change in BS was found to be significant (Table 5).…”
Section: Discussionsupporting
confidence: 85%
“…In all these studies change in BS was found to be significant after mifepristone except the study by Sharma et al probably because in this study assessment was done after 24 hours unlike other studies (48 hours) ( Table 6). 12 In the present study 36% subjects in group A and 14% subjects in group B went into labour during the ripening phase. Group B was comparable to the study by Meetei et al (who had kept Foley's for 12 hours).…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations